Induction therapy with the MATRix regimen in patients with newly diagnosed primary diffuse large B‐cell lymphoma of the central nervous system – an international study of feasibility and efficacy in routine clinical practice. (29th January 2020) - Schorb, Elisabeth; Fox, Christopher P.; Kasenda, Benjamin; Linton, Kim; Martinez‐Calle, Nicolas; Calimeri, Teresa; Ninkovic, Slavisa; Eyre, Toby A.; Cummin, Tom; Smith, Jeffery; Yallop, Deborah; De Marco, Beatrice; et al.
Summary: The MATRix chemoimmunotherapy regimen is highly effective in patients with newly diagnosed primary diffuse large B‐cell lymphoma of the central nervous system (PCNSL). However, nothing is known about its feasibility and efficacy in everyday practice, where patients are more often older/frailer than those enrolled in clinical trials. We conducted a retrospective study addressing tolerability/efficacy of MATRix in 156 consecutive patients with newly diagnosed PCNSL treated outside a clinical trial. Median age and ECOG Performance Status of considered patients were 62 years (range 28–78) and 2 (range 0–4). The overall response rate after MATRix was 79%. Nine (6%) treatment‐related deaths were recorded. After a median follow‐up of 27.4 months (95% confidence interval [CI] 24.4–31.9%), the two‐year progression‐free and overall survival were 56% (95% CI 48.4–64.9%) and 64.1% (95% CI 56.7–72.5%) respectively. Patients not eligible for the IELSG32 trial were treated with lower dose intensity and had substantially worse outcomes than those fulfilling inclusion criteria. This is the largest series of PCNSL patients treated with MATRix outside a trial and recapitulates the IELSG32 trial outcomes in the non‐trial setting for patients who fit the trial criteria. These data underscore the feasibility and efficacy of MATRix as induction treatment for fit patients in routine practice.